American sociology, realism, structure and truth: an interview with Douglas V. Porpora. Issue 5 (19th October 2020) - Porpora, Douglas V.; Morgan, Jamie
ABSTRACT: In this wide-ranging interview Professor Douglas V. Porpora discusses a number of issues. First, how he became a Critical Realist through his early work on the concept of structure. Second, drawing on his Reconstructing Sociology, his take on the current state of American sociology. This leads to discussion of the broader range of his work as part of Margaret Archer's various Centre for Social Ontology projects, and on moral-macro reasoning and the concept of truth in political discourse.